2021
DOI: 10.1177/14034948211039397
|View full text |Cite
|
Sign up to set email alerts
|

Variation in disease in children according to immigrant background

Abstract: Background: A growing proportion of children born in Europe are born to immigrant parents. Knowledge about their health is essential for preventive and curative medicine and health services planning. Objective: To investigate differences in diagnoses given in secondary and tertiary healthcare between Norwegian-born children to immigrant and non-immigrant parents. Methods: Data from the Medical Birth Registry of Norway, the Norwegian Patient Registry and Statistics Norway were linked by the national personal id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, the Norwegian study reported an increased risk of specific infections, for example, tuberculosis. 5 The ability of sociodemographic variables to discriminate between children with and without infections was poor indicating that a small proportion of the individual risk of infection was due to the social context. 14 Consequently, our results support broad public health policies reaching all children over interventions targeting children in high-risk groups.…”
Section: Original Researchmentioning
confidence: 99%
“…However, the Norwegian study reported an increased risk of specific infections, for example, tuberculosis. 5 The ability of sociodemographic variables to discriminate between children with and without infections was poor indicating that a small proportion of the individual risk of infection was due to the social context. 14 Consequently, our results support broad public health policies reaching all children over interventions targeting children in high-risk groups.…”
Section: Original Researchmentioning
confidence: 99%
“…Children who had a specific infection diagnosis at least once during the specified age and time frame were classified as having the respective diagnosis. Categories of infectious diseases corresponded to our previous article [16], but we did not include separate categories for four diagnostic categories with a low number of cases; tuberculosis, infections of the central nervous system, fungal and parasitic infections and genital infections (all with N < 3500). All 11 categories of infection diagnoses are included in the variable total infections.…”
Section: Variablesmentioning
confidence: 99%
“…Each participant was followed from 2008 or year of birth (if later than 2008) until year of diagnosis, year of death, year of reaching 10 years of age (if earlier than 2018), or until the end of 2018. Analyses were performed in STATA 16.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are more likely to report being alone and being bullied; on the other hand, they get along better with adults than with their peers and are more helpful and sharing with others [4,5]. Children of migrants did not have overall worse health than children without migrant background, but the distribution of health problems varied between groups [6]. A key take- away from the majority of the articles is that social inequalities (as measured by integration, language, length of stay, and working role) is the main explanation for differences observed.…”
mentioning
confidence: 99%